AI-generated journalism: Do the transparency provisions in the AI Act give news readers what they hope for? - Stanislaw Piasecki; Sophie Morosoli; Natali Helberger; Laurens Naudts (Internet Policy Review, 2024)
Issues linked to the increasing presence of AI-generated content in people's lives, and the importance of being able to effectively navigate and distinguish such content, are inherently linked to transparency, a notion that our study focuses on by evaluating Art. 50 of the AI Act. This article is a call for action to take the interests of end users into account when specifying AI Act's transparency requirements. It focuses on a specific use case - media organisations producing text with the help of generative AI. We argue that in its current form, Art. 50 leaves many uncertainties and risks doing too little to protect natural persons from manipulation or to empower them to take protective actions. The article combines documental and survey data analysis (based on a sample representative of the Dutch population) to propose concrete policy and regulatory recommendations on the operationalisation of the AI Act's transparency obligations. Its main objective is to respond to the following question: how to reconcile AI Act's transparency provisions applicable to digital news articles generated by AI with news readers' perceptions of manipulation and empowerment?
Keywords: 300; Transparency; AI Act; Media; Generative AI; Journalism